Cryptotanshinone Attenuates Oxygen-Glucose Deprivation/ Recovery-Induced Injury in an in vitro Model of Neurovascular Unit - Zhao, Hongye; Zheng, Tiezheng; Yang, Xiaohan; Fan, Ming; Zhu, Lingling; Liu, Shuhong; Wu, Liying; Sun, Changkai (Frontiers in Neurology, 2019)
Cryptotanshinone (CTs), an active component isolated from the root of Salvia miltiorrhiza (SM), has been shown to exert potent neuroprotective property. We here established an oxygen-glucose deprivation/recovery (OGD/R)-injured Neurovascular Unit (NVU) model in vitro to observe the neuroprotective effects of CTs on cerebral ischemia/reperfusion injury (CIRI), and explore the underlying mechanisms. CTs was observed to significantly inhibit the OGD/R-induced neuronal apoptosis, and decease the activation of Caspase-3 and the degradation of poly-ADP-ribose polymerase (PARP), as well as the increase of Bax/Bcl-2 ratio in neurons under OGD/R condition. The inhibitory effects of CTs on neuron apoptosis were associated with the blocking of mitogen-activated protein kinase (MAPK) signaling pathway. CTs also remarkably ameliorated OGD/R-induced reduction of transepithelial electrical resistance (TEER) values and the increase of transendothelial permeability coefficient (Pe) of sodium fluorescein (SF) by upregulating the expression of ZO-1, Claudin-5, and Occludin in brain microvascular endothelial cells (BMECs), which might be related to the down-regulation of matrix metalloproteinase (MMP)-9 expression. Based on these findings, CTs may play a neuroprotective role in OGD/R injure in NVU models in vitro by inhibiting cell apoptosis and alleviating the damage of blood-brain barrier (BBB).